The price setting behaviour of Spanish firms: evidence from survey data - Luis J. Álvarez; Ignacio Hernando (European Central Bank (ECB), 2005)
This paper reports the results of a survey carried out by the Banco de Espa\~na on a sample of around 2000 spanish firms to deepen the understanding of firms' price setting behaviour. The main findings may be summarised as follows. Most Spanish firms are price setters that use predominantly state-dependent rules or a combination of time- and statedependent rules when reviewing their prices. Changes in costs are the main factor underlying price increases, whereas changes in market conditions (demand and competitors' prices) are the main driving forces of price decreases. The degree of price flexibility is directly related to the share of energy inputs over total costs and to the intensity of competition, whereas it is inversely linked to the labour share. The three theories of price stickiness that receive the highest empirical support are implicit contracts, coordination failure and explicit contracts.
Keywords: D40; E31; 330; price setting; Price stickiness; survey data; Preismanagement; Preisrigidität; Spanien